Planned combined onco-plastic (COP) surgical approach improves oncologic outcomes in soft tissue sarcomas. Issue 2 (February 2021) - Brown, A.; Spazzoli, B.; Mah, E.; May, D.; Chu, J.; Spelman, T.; Choong, P.; Di Bella, C.
Abstract: Background: Combined modality of radiotherapy and surgery is the standard of treatment of soft tissue sarcomas (STS). The goal of this study was to assess whether a Combined Onco-Plastic (COP) surgical approach in the setting of neo-adjuvant radiotherapy can improve the oncologic outcomes of STS and reduce the rate of wound complications. Methods: We performed a retrospective review of all patients with STS treated at a single sarcoma centre (St Vincent's Hospital, Melbourne) between 2007 and 2018. Patients were stratified into two groups based on whether they have received the COP approach or were closed primarily by the orthopaedic surgeon. We analysed oncological outcomes and rate of wound complications. Results: A total of 546 patients with comparable demographics and tumor characteristics were included. The COP approach was performed in 75.6% of the patients. Wide margins were obtained in 97.4% of the cases, and this was significantly higher in the COP group (p < 0.001). The cumulative rate of local recurrence was 4.9%, with a 52% risk reduction in the COP approach, although this reduction was not significant (HR = 0.48; 95% CI 0.21–1.06; p = 0.070). The COP approach had better disease free survival (DFS) (aHR 1.86, 95% CI 1.45–2.37; p < 0.001) and Overall survival (risk of death aHR 0.49; 95% CI 0.30–0.79; p = 0.004). The overall wound complication rate was 18.6% with no difference between the two groups. Conclusion: A planned collaboration between the orthopaedic oncologist and the plastic surgeon is beneficial in the treatment of STS after neo-adjuvant radiotherapy, allowing remarkably good oncological outcomes and a low rate of wound complications.